Key categories in the study of religion: contexts and critiques - King, Rebekka (NAASR working papers, 2022)
"Key Categories in the Study of Religion builds upon the groundwork laid by previous NAASR Working Papers titles in order to bring us full circle to the symbiotic relationship between context and critique. This volume assembles diverse sets of data to consider pertinent categories in which critique occurs"--